2018
DOI: 10.1186/s12933-018-0753-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma copeptin, kidney disease, and risk for cardiovascular morbidity and mortality in two cohorts of type 2 diabetes

Abstract: BackgroundCardiovascular disease and kidney damage are tightly associated in people with type 2 diabetes. Experimental evidence supports a causal role for vasopressin (or antidiuretic hormone) in the development of diabetic kidney disease (DKD). Plasma copeptin, the COOH-terminal portion of pre-provasopressin and a surrogate marker of vasopressin, was shown to be positively associated with the development and progression of DKD. Here we assessed the association of plasma copeptin with the risk of cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 67 publications
0
28
0
2
Order By: Relevance
“…Then, when physiologists discovered that both LOW and HIGH exhibited a normal P OSM and body weight (i.e., suggesting euhydration) but that LOW had higher plasma AVP compared to HIGH, they began to ask, "What are the possible mechanisms of long-term negative health effects that result from habitually consuming a small volume of water?". This prompted human epidemiological studies which eventually revealed statistically significant links between elevation of plasma AVP or copeptin (i.e., released in equimolar quantities with AVP) and increased risk of developing diabetes [29][30][31], hyperglycemia [32], insulin resistance, metabolic syndrome [33,34], abdominal obesity [35], stroke, cardiovascular disease, cardiovascular events, cardiovascular death [7,[36][37][38], hypertension [34] and kidney disease [38][39][40]. In some of these studies, the data of thousands of adults were involved in the analysis, providing robust statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Then, when physiologists discovered that both LOW and HIGH exhibited a normal P OSM and body weight (i.e., suggesting euhydration) but that LOW had higher plasma AVP compared to HIGH, they began to ask, "What are the possible mechanisms of long-term negative health effects that result from habitually consuming a small volume of water?". This prompted human epidemiological studies which eventually revealed statistically significant links between elevation of plasma AVP or copeptin (i.e., released in equimolar quantities with AVP) and increased risk of developing diabetes [29][30][31], hyperglycemia [32], insulin resistance, metabolic syndrome [33,34], abdominal obesity [35], stroke, cardiovascular disease, cardiovascular events, cardiovascular death [7,[36][37][38], hypertension [34] and kidney disease [38][39][40]. In some of these studies, the data of thousands of adults were involved in the analysis, providing robust statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their participants were younger than ours, and age and pubertal status are well-known factors affecting copeptin concentrations. 21 In adults, several studies have demonstrated that copeptin concentrations are elevated in people with T1D, 10 T2D, 11 and DKD and CVD. 22 A growing body of epidemiological research also indicates that high copeptin concentrations predict future CVD and all-cause mortality in adults with diabetes, yet the data are less consistent in the non-diabetes population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to AVP, copeptin is stable for days, easily measured and mimics fluctuations in AVP concentration . Several studies have demonstrated relationships between increased copeptin and the development or worsening of CVD and DKD in cohorts of adults with diabetes . In addition to water reabsorption in the collecting ducts via vasopressin‐2 (V2) receptor activity, AVP stimulates V1a receptor at arterial smooth muscles and the liver as well as V1b receptor at hypothalamus, resulting in vasoconstriction, hepatic glucose production and cortisol secretion, thereby hastening cardiorenal complications in diabetes .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations